Atendimento psicológico na abordagem centrada na pessoa : experiências com orientação profissional em um serviço-escola - Rocha, Jaqueline Correa (2021)
This research, organized in an exploratory design, presents the theme of psychological care in the Person Centered Approach of a University Clinic, specifically for people enrolled in this service who reported, in their complaints and demands, themes on professional issues. It was submitted and approved by the Ethics and Research Committee – Humanities/UFMT. For the research, a data survey was carried out in the registration forms and screening interviews of people who signed up for psychological care in the second semester of 2019, including adults and adolescents of both sexes. Based on the data collected, it was possible to characterize the clientele and categorize information such as age, sex, education, complaint, feelings in the presence of the complaint, ways of dealing with the complaint, daily activities and the existing social support. After this data survey, the registration forms and screening interviews of clients who had not yet been attended and which brought professional themes as a source of suffering were selected. Subsequently, Psychological Care in the Person Centered Approach was offered for these subscribers, individually, for at least 10 sessions, in the online modality because the COVID-19 pandemic which made it impossible to collect data at the University Clinic. The sessions were recorded by the psychologist researcher in a field diary and each client-participant was asked to produce, at the end of each session, a ‘Sense's version’, a methodology developed under the Person-Centered Approach for data survey. The data analysis from the registration forms and screening interviews was carried out using a quantitative-interpretative model, and is presented as part of the description of the place where this research was carried out, and the understanding of the psychotherapy sessions followed a qualitative proposal, through which the psychologist researcher was able to evidence theoretical and methodological aspects present in the sessions, such as facilitating attitudes, family relationships, self-perception in psychotherapy and human development, as well as the development of treatments and their consequences in terms of gains in integral health for the client-participants.